From the Discussions between Lelia Basso and Czechoslovak Researchers (Czech Journal of International Relations, 1966)
On September 12, 1966, the Constitution for International Politics and Economy welcomed the chairman of the Italian Socialist Party of Proletarian Unity, Lelio Basso, from September 2 to 15 at the invitation of UV KSC in Czechoslovakia. Already in 1965, he presided over ÚMPE on the problems of the Italian labor movement T. Vecchietti, general the secretary of this small but important Italian party, which has meanwhile been honored in the municipal and guilty elections (in June 1966) it won as a valid left-wing force. Lelio Basso introduced this year's talk, which, in addition to UMPE employees, also took part members of other scientific workplaces, with a lecture on the role of social democracy in Western Europe.